Kontribusi persepsi tentang manfaat praktek, motivasi belajar, dan kecukupan alat/bahan terhadap prestasi belajar mahasiswa Pendidikan Teknik Mesin Fakultas Teknik UNM - Mardi Syahrir; Asmah Adam (Seminar Nasional LP2M UNM, 2019)
The analysis used in this study is to use correlation analysis, which aims to determine the contribution of perceptions about the benefits of practice on learning achievement, then learning motivation towards learning achievement. Furthermore perceptions about the adequacy of tools / materials for learning achievement. The results of this study indicate that perceptions of the benefits of practice contribute to learning achievement with the value of the correlation coefficient = 0.55 which indicates the level of the relationship of the medium and significant categories.Then learning motivation contributes to learning achievement with the correlation coefficient r = 0.58 which indicates the level of the relationship of the medium and significant categories.Furthermore, perceptions of the adequacy of tools / materials contribute to learning achievement with a correlation coefficient value of r = 0.54 which indicates the level of relationship between moderate and significant categories. While perceptions of the benefits of practice, motivation to learn, and perceptions of the adequacy of tools / materials on learning achievement together influence the learning achievement with multiple correlation coefficients R = 0.765 which indicates a level of strong and significant relationships. From these findings, it can be concluded that, learning achievement is influenced by perceptions about the benefits of practice, motivation to learn, and perceptions of the adequacy of tools / materials. Therefore it is necessary to increase the three independent variables.